Rapid isolation in large numbers of intact, viable, individual hair follicles from skin: biochemical and ultrastructural characterization - Green, M R; Clay, C S; Gibson, W T; Hughes, T C; Smith, C G; Westgate, G E; White, M; Kealey, T (Journal of investigative dermatology, 1986)
A rapid, novel method is described by which large numbers of intact, viable, individual hair follicles may be isolated from rat skin. Follicles are freed from the surrounding connective tissue by shearing, which is effected by repeated cutting with a loosely fitting pair of scissors, and collected individually under liquid using gentle aspiration. Ultrastructural analysis indicates that the follicles are sheared away from the surrounding dermis in the region of the connective tissue capsule which encircles the hair. The follicles appear viable by light and electron microscopy and, within 2 h of isolation, retain the capacity to incorporate [3H]thymidine into DNA and [35S]methionine into proteins as judged by autoradiography. A histologic comparison indicates that the structural integrity of follicles isolated by this new method is significantly superior to those plucked from the animal at the same time. The method affords the isolation of large numbers of hair follicles, without resort to enzyme treatments, suitable for biologic studies in the absence of other skin appendages and dermis.